2011
DOI: 10.14245/kjs.2011.8.4.272
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Spinal Epidural Hematoma: A Retrospective Study on Prognostic Factors and Review of the Literature

Abstract: ObjectivesThe spontaneous spinal epidural hematoma (SSEH) is a rare clinical entity. Patients typically present with sudden onset back pain followed by neurological deficits.MethodsDiagnosis of SSEH is usually made with MRI and standard treatment is surgical evacuation. In 1996, Groen published the most comprehensive review on the SSEH in which he analyzed 333 cases. We review 104 cases of SSEH presented in the English literature since the last major review and add three of our own cases, for a total of 107 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…One of the first extensive reviews on spontaneous spinal epidural hematoma was reported by Groen in 1996 (15). A more recent one, by Kim et al in 2011 (9), identified a total of 107 cases of spontaneous spinal epidural hematoma published in neurosurgical series between 1996 and 2011.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the first extensive reviews on spontaneous spinal epidural hematoma was reported by Groen in 1996 (15). A more recent one, by Kim et al in 2011 (9), identified a total of 107 cases of spontaneous spinal epidural hematoma published in neurosurgical series between 1996 and 2011.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been increased reports of spontaneously resolving spinal epidural hematomas, due to quick diagnosis by higher resolution MRI (9). A conservative treatment under close neurologic observation is recommended for patients with no, or mild neurologic deficits and for patients who show definite progressive improvement prior to the MRI diagnosis of SCEH (9,13,27).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations